1999
DOI: 10.1017/s0967199499000702
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intracellular content of glutathione and thiols associated with γ-glutamyl cycle during sperm penetration and pronuclear formation in rat oocytes

Abstract: The content of glutathione and other thiols in rat eggs was examined during sperm penetration and pronuclear formation by high-performance liquid chromatography with fluorescence detection. Reduced glutathione (GSH) content was higher in unfertilised oocytes (8.50 ± 0.29 pmol/egg) and penetrated eggs with a decondensed sperm nucleus (DSH eggs; 7.72 ± 0.56 pmol/egg) than eggs at the pronuclear stage (PN eggs; 5.93 ± 0.10 pmol/egg). The content of oxidised glutathione (GSSG) was not different among experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Spectrophotometry of intracellular extracts, on the other hand, has shown that up to 30 pmol/oocyte of glutathione (GSH) are contained in oocytes of goat34 and pig3536 and can change in reaction to environment and developmental stage37. Variations of a few pmol/oocyte of GSH in time scales of the order of several hours have been reported in hamster38 and rat39 oocytes. In these studies, the intracellular GSH content and its evolution is directly measured, but the ensemble measurements hide possible heterogeneities among single entities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Spectrophotometry of intracellular extracts, on the other hand, has shown that up to 30 pmol/oocyte of glutathione (GSH) are contained in oocytes of goat34 and pig3536 and can change in reaction to environment and developmental stage37. Variations of a few pmol/oocyte of GSH in time scales of the order of several hours have been reported in hamster38 and rat39 oocytes. In these studies, the intracellular GSH content and its evolution is directly measured, but the ensemble measurements hide possible heterogeneities among single entities.…”
Section: Discussionmentioning
confidence: 98%
“…The direct application of NMR on single embryos using miniaturized high sensitivity probes is potentially advantageous for this aim. We suggest that systematic and extensive NMR studies on single cultured ova may provide new data that could shed light on cryptic processes involved in embryonic development3233343536373839 and provide new methodologies to estimate embryonic health3740.…”
Section: Discussionmentioning
confidence: 99%